PENGUSUNGAN POLA PIKIR POSITIVISME HUKUM DALAM PERKARA KORUPSI - Ricca Anggraeni (Komisi Yudisial RI, 2011)
ABSTRACTSlogan that power tends to corrupt is not just a phrase. Several cases of corruption seem to prove that power has encouraged persons to engage in corruption. Erradicating corruption requires extraordinary efforts of law enforcers. However, again the fact shows that many law enforcers are dragged into corruption practices. In fact, they often use the law to neatly wrap their crimes. Packaging is done through a court decision. Judge as the spearhead of law enforcement in Indonesia should be given a maximum role in enforcing the law. That role should have two values of upholding the value of justice and law enforcement. In some cases of corruption, the perpetrators were given lenient sentences, even released. Mild sanctions against the perpetrators of corruption are also reflected in the case of corruption committed by the Head of Semudun Regional Water Company (PDAM Semudun), Pontianak regency. Mild sanctions for the accused is caused by the tendency of judges who carry the mindset of schools of legal positivism, that is by simply using the law as a source of reference to rely on a monolithic interpretation methods.Keywords: corruption, legal positivism, law enforcement, justice. ABSTRAKKekuasaan cenderung melakukan korupsi bukan hanya slogan semata. Beberapa kasus korupsi menunjukkan bahwa seseorang yang memiliki kekuasaan melakukan korupsi, oleh sebab itu memangkas korupsi membutuhkan perjuangan dan penegakan hukum yang ektraordinary. Sebaliknya, fakta berbicara lain pada saat hakim justru memberikan hukuman minimal bukan maksimal, dan bahkan dalam beberapa kasus korupsi bahkan terdakwa dilepaskan. Kasus korupsi yang dilakukan oleh pejabat perusahaan perairan di Kalimantan yang dihukum ringan memperlihatkan hal itu. Itu terjadi karena hakim mengunakan pendekatan legalistik dan metode interpretasi monolistik. Putusan hakim cenderung mengakomodasikan nilai-nilai hukum saja, dan mengeliminasi nilai-nilai keadilan sebagai tujuan akhir putusan hakim. Kata kunci: korupsi, legal positivism, penegakan hukum, keadilan.